PEMANFAATAN SISTEM INFORMASI APLIKASI ONLINE PUBLIC ACCESS CATALOGUE (OPAC) PADA PERPUSTAKAAN STAIN BATUSANGKAR - Manajer Jurnal (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
System Online Public Access Catalogue (OPAC) is a system of computer aided catalogs in electronic or digital form that allows users to access and search the information in the form of library materials available in the library online and realtime. This study used a quantitative approach to the descriptive type and examined benefit Online Public Acsses Catalogue (OPAC) in STAIN Library. The informant was consisted of users of the system taken Online Public Access Catalog (OPAC) in the Library of the STAIN Batusangkar. This research focused on student that use Online Public Acsses Catalogue (OPAC). The data analyisis of this research was related to Miles & Hubberman model (Reduction data, show data and conclusion). Data were collected through observation and interview. The results revealed that Online Public Acsses Catalogue (OPAC) gave users benefit, ease students to find all books in STAIN library fastly. The quality of information and quality of service has a good level of satisfaction so it increases students’ satisfaction.Keyword: The Application of Information System, Online Public Access Catalogue, Library, State Institute of Islamic Studies, Batusangkar